Association of Raised C-Reactive Proteins With Prolonged ICU Stay in Children with Bronchopneumonia: A Cross Sectional Study - Shazia Rizwan; Sara Hassan; Madiha Iqbal; Sobia Shahalam; Tayyaba Noor; Rizwan Waseem (University of Lahore, 2024)
Objective  To study the association of raised CRP with prolonged ICU stay in children with bronchopneumonia at Ghurki Trust Teaching Hospital, Lahore, Pakistan. Methodology This cross-sectional study was conducted in Paediatric Intensive Care Unit of Ghurki Trust Teaching Hospital, Lahore, Pakistan, for a duration of six months (June 2023 to December 2023). Out of 127 children admitted into ICU, 82 met the inclusion criteria, aged 2-60 months, diagnosed with bronchopneumonia. Upon admission, blood sample was taken for CRP levels and these levels were correlated with ICU stay, TLC count, O2 dependency, and antibiotics duration of the patients. Patients were divided into five groups based on CRP counts. CRP counts less than 0.3 mg/dL were taken as normal. CRP counts from 0.4-0.9 mg/dL were taken as mild, 1-10 mg/dL were considered moderate, 11-49 mg/dL were considered marked, and ≥50 mg/dL were considered severe. Results Out of 82 patients, 45 (54.88%) were males and 37 (45.12%) were females. This study found that raised CRP was present in 73 (89.02%) out of 82 children (p<0.04). Amongst 73 (89.02%), 08 (10.96%) patients had mild elevation of CRP, 36 (49.32%) had moderate elevation, 22 (30.14%) had marked, 07 (9.59%) had severe elevation. Moreover, a direct relation was observed among CRP and ICU stay (3.82±3.12), O2 requirements (3.72±3.07), TLC (13.36±5.18), antibiotic treatment duration (9.52±3.94) of broncho pneumonic patients. Conclusion Higher CRP levels significantly result in longer ICU stays and higher oxygen requirements in children with bronchopneumonia.